2021
DOI: 10.1111/cdep.12431
|View full text |Cite
|
Sign up to set email alerts
|

Advancing developmental intergroup perspectives on social class

Abstract: Globally, children and adolescents are growing up in societies marked by stark economic inequality. Along with a robust body of scholarship highlighting the importance of economic security for children's health and well-being, researchers are beginning to examine how children and adolescents think and feel about their own and others' economic circumstances or social class position (Ruck et al., 2019). Reflecting diverse theoretical traditions, recent studies have, for example, investigated social class identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Reflecting these shifts in social group preferences, young children distributed more resources to White peers, especially if they were also rich, and reasoned about their own personal preferences (e.g., "I like him more") but participants in middle childhood distributed more to rich peers and reasoned about their social class group preferences (e.g., "[She] has better stuff and I like that"). One interpretation is that, by middle childhood, participants were becoming aware of broader US national narratives that esteem the rich and chastise the poor (Mistry et al, 2021). Another interpretation is that children's early concepts of social class were primarily material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting these shifts in social group preferences, young children distributed more resources to White peers, especially if they were also rich, and reasoned about their own personal preferences (e.g., "I like him more") but participants in middle childhood distributed more to rich peers and reasoned about their social class group preferences (e.g., "[She] has better stuff and I like that"). One interpretation is that, by middle childhood, participants were becoming aware of broader US national narratives that esteem the rich and chastise the poor (Mistry et al, 2021). Another interpretation is that children's early concepts of social class were primarily material.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, US children's social class stereotypes change meaningfully in both scope and content between middle and late childhood (Mistry et al, 2021), and it is well established that White children's racial prejudice peaks in middle childhood (Raabe & Beelmann, 2011). Moreover, recent studies suggest that late childhood is an important developmental period when children's greater awareness of equity issues in their own communities enables them to begin to see parallels with distributive justice issues that they can personally address (Elenbaas & Mistry, 2021).…”
Section: Theoretical Framework: Social Reasoning Developmental Modelmentioning
confidence: 99%
“…As Mistry et al (2021) observed, representations of social class groups are culturally embedded within societies. Language, news reports, drama and humour convey rich, but often complex and contradictory, information about social class so most members of society will be familiar with these representations.…”
Section: Moral Orientation Experiences and Social Contextmentioning
confidence: 99%
“…Once children are aware of social class, they are motivated to identify with positively distinct social class groups (Mistry et al, 2021), and the need to maintain a positive social identity can then result in prejudice and discrimination towards outgroups. Very little research has investigated the development of inter‐class prejudice in children (Mistry et al, 2021), but young children (4–6 years) demonstrate a preference for friendship with wealthier children (Shutts et al, 2016), and older children (8–14 years) anticipate that social class groups will favour members of their own social class (Elenbaas & Killen, 2019). Friendship preferences lead to exclusion and low‐income children are particularly likely to experience exclusion as they lack the financial resources to participate in many activities (Ridge, 2011).…”
Section: Social Identitiesmentioning
confidence: 99%
“…Children’s perceptions of teacher bias involve multiple forms of judgment including the role of authority for decision making, as well as the recognition of unfair treatment that results from group norms and social inequalities. Recently, research has examined when children view group-level social inequalities as unfair and whether they desire to rectify such disparities (Elenbaas, 2019; Mistry et al, 2021). These data are relevant for understanding how children perceive classroom bias and for creating inclusive classrooms.…”
Section: Objectives Of This Papermentioning
confidence: 99%